2020
DOI: 10.1002/psp4.12520
|View full text |Cite
|
Sign up to set email alerts
|

A Physiologically‐Based Quantitative Systems Pharmacology Model of the Incretin Hormones GLP‐1 and GIP and the DPP4 Inhibitor Sitagliptin

Abstract: Incretin hormones glucagon‐like peptide‐1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP) play a major role in regulation of postprandial glucose and the development of type 2 diabetes mellitus. The incretins are rapidly metabolized, primarily by the enzyme dipeptidyl‐peptidase 4 (DPP4), and the neutral endopeptidase (NEP), although the exact metabolization pathways are unknown. We developed a physiologically‐based (PB) quantitative systems pharmacology model of GLP‐1 and GIP and their metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…According to this model, dapagliflozin is more beneficial to patients with more inadequate glycemic control by insulin [ 77 ]. Another model (#28) focuses on several protagonists in glucose levels after food consumption [ 78 ]. The incretin hormones, glucagon-like peptide-1 (GLP-1), glucose-dependent insulinotropic polypeptide (GIP) catalyzed by enzyme dipeptidyl-peptidase 4 (DPP4), and the neutral endopeptidase (NEP) stimulate insulin release to lower glucose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this model, dapagliflozin is more beneficial to patients with more inadequate glycemic control by insulin [ 77 ]. Another model (#28) focuses on several protagonists in glucose levels after food consumption [ 78 ]. The incretin hormones, glucagon-like peptide-1 (GLP-1), glucose-dependent insulinotropic polypeptide (GIP) catalyzed by enzyme dipeptidyl-peptidase 4 (DPP4), and the neutral endopeptidase (NEP) stimulate insulin release to lower glucose.…”
Section: Resultsmentioning
confidence: 99%
“…By modeling GLP-1 and GIP dynamics, and PK/PD of DPP4 inhibitors, model #28 showed that inhibition of DPP4 occurs in a dose-dependent manner. Still, the highest dose of DDP4 inhibitor stimulated a high GLP-1 secretion, suggesting the triggering of alternative pathways upon DPP4 inhibition [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…GLP-1 has been identifed as an incretin hormone produced by L cells in the intestine and neurons in the nucleus of the solitary tract (NTS) of the brainstem; together with GLP-1 receptor (GLP-1R), this hormone enhances glycemic control [18][19][20]. DPP-IV activity is associated with the Glp-1 level in plasma [21,22] because native GLP-1 undergoes swift degradation by enzyme dipeptidyl peptidase-IV (DPP-IV) [23]. Stable GLP-1 mimetics and DPP-IV inhibitor drugs have been introduced into clinical practice to treat obesity and T2DM [24].…”
Section: Discussionmentioning
confidence: 99%